ANALYSIS OF THE INFLUENCE OF FOREIGN DIRECT INVESTMENT, LABOR PRODUCTIVITY AND TECHNOLOGYON ECONOMIC GROWTH - Loso Judijanto; Ajeng Faizah Nijma Ilma; Gautama Sastra Waskita (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Foreign investment, labor productivity and technology are key factors that can significantly influence economic growth. An important factor in a nation's economic development is foreign direct investment. This involves investing foreign assets into domestic structures, equipment, and organizations. Research on the Indonesian economy shows that FDI has a significant impact on economic growth. FDI can also increase the productivity and macroeconomic stability of the recipient country so that this source of funds is considered to have great potential as a driving force for the economy and is believed to be relatively safe for a country because it is a long-term investment. Macroeconomic indicators like unemployment, pricing levels, and economic growth can be used to assess a nation's economic performance. Economic growth is mostly driven by labor productivity. Therefore, policies and strategies that aim to increase productivity are essential for achieving sustained and inclusive economic development. The influence of technology on economic growth can be seen from various perspectives. Based on available information, technology has a significant impact in driving a country's economic growth.